Antimicrobial stewardship programs in adult intensive care units in Latin America: Implementation, assessments, and impact on outcomes - Quirós, Rodolfo E (2022)
Objective: To assess the impact of antimicrobial stewardship programs (ASPs) in adult medical-surgical intensive care units (MS-ICUs) in Latin America. Design: Quasi-experimental prospective with continuous time series. Setting: The study included 77 MS-ICUs in 9 Latin American countries. Patients: Adult patients admitted to an MS-ICU for at least 24 hours were included in the study. Methods: This multicenter study was conducted over 12 months. To evaluate the ASPs, representatives from all MS-ICUs performed a self-assessment survey (0-100 scale) at the beginning and end of the study. The impact of each ASP was evaluated monthly using the following measures: antimicrobial consumption, appropriateness of antimicrobial treatments, crude mortality, and multidrug-resistant microorganisms in healthcare-associated infections (MDRO-HAIs). Using final stewardship program quality self-assessment scores, MS-ICUs were stratified and compared among 3 groups: ≤25th percentile, >25th to <75th percentile, and ≥75th percentile. Results: In total, 77 MS-ICU from 9 Latin American countries completed the study. Twenty MS-ICUs reached at least the 75th percentile at the end of the study in comparison with the same number who remain within the 25th percentile (score, 76.1 ± 7.5 vs 28.0 ± 7.3; P <.0001). Several indicators performed better in the MS-ICUs in the 75th versus 25th percentiles: antimicrobial consumption (143.4 vs 159.4 DDD per 100 patient days; P <.0001), adherence to clinical guidelines (92.5% vs 59.3%; P <.0001), validation of prescription by pharmacist (72.0% vs 58.0%; P <.0001), crude mortality (15.9% vs 17.7%; P <.0001), and MDRO-HAIs (9.45 vs 10.96 cases per 1,000 patient days; P =.004). Conclusion: MS-ICUs with more comprehensive ASPs showed significant improvement in antimicrobial utilization.